Anthropology of Composite Images of the Etruscan Portrait - Shpak, Larisa Iu. (Actual Problems of Theory and History of Art, 2023)
In the invaluable for the physical anthropologist gallery of ancient faces represented by fine arts the Etruscan portrait occupies a special place. A large number of sculptural images of Etruscans are made in the genre of physiognomic portrait, which naturalistically conveys individual elements of the appearance, important for the descriptive analysis of morphological variability. Craniological and paleogenetic data regarding the origin of the Etruscans are very contradictory. In the scientific literature, there are practically no examples of works on the anthropological description of the appearance of the Etruscans based on the analysis of groups of various artistic sources and their visualization. The aim of the study was to obtain anthropological characteristics and composite portraits of three different groups of Etruscan artistic sources and to interpret them in the context of the Etruscan ethnogenesis. Funerary painting (6th‒3rd centuries BC) and funeral sculpture (3rd‒1st centuries BC), as well as votive sculpture of the 5th‒1st centuries BC (votive terracotta heads), were the research materials utilized. The studied groups of images have different informative value and reveal different degree of polymorphism regarding the characters of facial morphology. The most reliable source of information is found in the funerary sculpture. Composite portraits based on three groups of pictorial sources show ambiguous results regarding anthropological type: the picturesque portrait aligns most closely with the description of the Mediterranean type, the votive portrait takes an intermediate position, and the portrait on sarcophagi is most closely connected with the description of the Alpine type. To obtain comparative information and enhance the interpretation of our results, it is necessary to conduct an anthropological research of the fine art of other ancient cultures within the Mediterranean region.
Keywords: physical anthropology; composite portrait; F. Galton method; ancient portrait; Etruscan portrait; Etruscan sarcophagi; Etruscan painting; votive terracotta heads; Etruscan ethnogenesis